Rekonstruksi Peran Judex Facti dalam Perkara Narkotika (Analisis Putusan Banding Nomor 130/PID.SUS/2023/PT DKI) - Muh Amin Saleh; Junet Hariyo Setiawan (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to analyze the reconstruction of the judex facti role by the High Court in narcotics cases involving law enforcement officials. Using a normative juridical approach, this study conducts an in-depth analysis of Appellate Court Decision Number 130/PID.SUS/2023/PT DKI in the case of Inspector General Teddy Minahasa Putra. The findings reveal that the High Court failed to carry out its corrective function substantively as a judex facti. The study identifies three fundamental weaknesses: first, factual reconstruction was not supported by scientific verification and in-depth evidence analysis; second, there was non-compliance with electronic evidence standards as stipulated in Supreme Court Regulation No. 4 of 2020 and the Electronic Information and Transactions Law; third, structural bias was evident in handling this institutional case. This research recommends comprehensive reforms in the electronic evidence system through amendments to the Criminal Procedure Code (KUHAP), standardization of digital chain of custody, and strengthening the impartiality of appellate courts. The study makes a significant contribution to the development of criminal procedure law in the digital era, particularly regarding the accountability of the appellate judiciary system.